2015
DOI: 10.15844/pedneurbriefs-29-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Occurrence of Febrile Seizures

Abstract: Investigators from University of Oulu, Finland, evaluated the diurnal and seasonal occurrence of the first febrile seizures (FS) in 461 children in a population-based study of 1522 children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
1
15
1
Order By: Relevance
“…2,21,38 Seasonal and diurnal variations in the occurrence of febrile seizures have been observed in studies from United States, Finland and Japan. [15][16][17][18] In this study seizures were more prevalent in the month of June (20%) that is in the monsoon season and is more frequent in the morning hours (43.3%) followed by night (25%) unlike a study from Finland where seizures were more prevalent in winter months and evening 15 and study from Iran showed that seizures occurred more in the afternoon and in winters. 18 Family history of seizure varied from 0.4% to as high as 20.6% of children with febrile seizure as reported in previous studies.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…2,21,38 Seasonal and diurnal variations in the occurrence of febrile seizures have been observed in studies from United States, Finland and Japan. [15][16][17][18] In this study seizures were more prevalent in the month of June (20%) that is in the monsoon season and is more frequent in the morning hours (43.3%) followed by night (25%) unlike a study from Finland where seizures were more prevalent in winter months and evening 15 and study from Iran showed that seizures occurred more in the afternoon and in winters. 18 Family history of seizure varied from 0.4% to as high as 20.6% of children with febrile seizure as reported in previous studies.…”
Section: Discussionmentioning
confidence: 86%
“…Studies have shown that febrile seizures tend to occur more in the winter months and are more common in the evening but some studies have shown that the majority of febrile seizures occur in the winter months but in the afternoon. [14][15][16][17][18] One-third of children who have a febrile seizure will have another one with another febrile illness. The younger the child is at the time of the first episode, the greater the risk is of recurrence.…”
mentioning
confidence: 99%
“…Race/ethnicity and hospital locations were significantly associated with FS severity. Several epidemiological studies have described the prevalence of FS [7,8,21,22]. In Europe and the USA, 2%-4% of all children experience at least one episode of FS before the age of 5 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of FS peaks at the age of 18 months, and is 2%-9% among all children [1][2][3][4][5]. The incidence is the highest among children living in Asian and Pacific Island countries, and is higher in boys than girls, with a male-to-female ratio of 1.1-2.0 [2][3][4][5][6][7][8]. In addition, seasonal variation has been reported in Finland, Japan, and the USA, and the highest incidence observed in winter, and the lowest in summer [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation